Formation of Health Care Cadres for High Risk Pregnant Women "Nginceng Resti Meteng" in Kuwasaran District, Kebumen Regency: Pembentukan Kader Kesehatan Pendamping Ibu Hamil Resiko Tinggi "Nginceng Resti Meteng" di Kecamatan Kuwasaran Kabupaten Kebumen - Astutiningrum, Diah; Ernawati, E`; Iswati, Ning (Prosiding University Research Colloquium, 2023)
The process of pregnancy is a physiological process, but over time pregnancy can turn into pathology. ANC visits as an effort to reduce maternal and infant mortality during pregnancy. The role of companion cadres is an important part of preparing for childbirth to prevent risks and changes in behavior in pregnant women in preparation for childbirth. found 5 high-risk pregnant women in the Kuwarasan Health Center area. The lack of information about care during pregnancy and monitoring from health workers is caused by the lack of routine pregnancy checks, and the absence of cadres to accompany high-risk pregnant women in the area. The method used is training for pregnant women cadres in screening high risk pregnant women, home visits screening pregnant women and evaluating cadres. The results of community service are the formation of health cadres to accompany high-risk pregnant women, increase the knowledge of cadres and the availability of learning media to educate the public about high-risk pregnancy care.